The Use of Instructional Media in PAI (Islamic Religious) Lesson in Elementary School - Nasih, Ahmad Munjin; Sultoni, Achmad; Maisyaroh, Maisyaroh; Fuad, Ah. Zakki; Rif’an, Ali (JPP (Jurnal Pendidikan dan Pembelajaran), 2017)
Abstract: The teaching of Islamic education in elementary school in Indonesia has not been widely explored by researchers, while this subject is particularly important in developing students’ character. This study aimed to describe the teaching of Islamic Education in elementary school in Malang, particularly in terms of the use of instructional media. Qualitative method with case study observational design and multi-site research design was chosen to meet the aim, including the use of structured-interview and observation as means of data collection. By using qualitative data analysis, it was found that (1) there were diverse teaching methods used by teachers, (2) teachers used various instructional media, both conventional and modern, (3) the quantity and quality of supporting facilities of the PAI lesson were considered sufficient, and (4) there were some internal as well as external factors that either supported or hampered the teaching of Islamic Education in elementary school.Keywords: elementary school, Islamic education, learningmediaAbstrak: Kajian mengenai pengajaran Pendidikan Agama Islam (PAI) di Sekolah Dasar selama ini relatif belum banyak dilakukan. Padahal sebagai mata pelajaran inti, PAI mempunyai peranan penting dalam pembentukan karakter siswa. Penelitian ini bertujuan menggambarkan bagaimana pembelajaran PAI di Sekolah Dasar di Malang Raya berlangsung, khususnya bagaimana penggunaan multimedia dalam proses pembelajaran. Untuk mencapai tujuan tersebut digunakan pendekatan kualitatif dengan rancangan studi kasus observasional dan multisitus. Teknik pengumpulan data yang dipilih adalah wawancara terstruktur dan observasi. Analisis data dilakukan secara kualitatif. Temuan penelitian ini menunjukkan bahwa (1) metode pembelajaran yang digunakan guru dalam mengajarkan PAI cukup variatif, (2) terdapat beragam media yang digunakan guru dalam pembelajaran PAI. Selain media konvensional, sebagian guru menggunakan multimedia modern, (3) fasilitas pendukung pembelajaran PAI di SD dapat dikatakan cukup memadai, dan (4) faktor pendukung maupun penghambat penggunaan media dalam pembelajaran PAI di SD bersumber dari internal sekolah dan luar sekolah.Kata kunci: media pembelajaran, pendidikan agama Islam (PAI), sekolah dasar